Efficacy of surgical treatment in patients with cervical spondylotic myelopathy - Ivetić Dražen; Pavlićević Goran; Kostić Dejan (Vojnosanitetski Pregled)
Background/Aim. Treatment options for cervical spondylotic myelopathy (CSM) are the topic for discussion due to the lack of controlled randomized prospective studies. Also, the natural history of CSM is unpredictable and the efficacy of surgical decompression is still controversial. The aim of this prospective study was to describe the results of surgical treatment of patients with CSM in a single institution. Methods. Fifty-nine patients with symptomatic CSM were enrolled in this single-center prospective study. At the end of the follow-up period of 12 months, 50 patients were analyzed. All patients were operated on; surgical decompression was performed by anterior or posterior surgical approach. Outcome evaluations were obtained preoperatively and 12 months postoperatively by using the following outcome measures: the modified Japanese Orthopedic Association (mJOA) scale, the Nurick score and the Neck Disability Index (NDI). The functional recovery ratio was calculated postoperatively by using Hirabayashi’s formula. Results. According to our results, significant improvements were detected in all outcome variables (mJOA score, Nurick score and NDI). Also, a statistically significant improvement was observed in all three categories of patients according to the preoperative mJOA score (mild, moderate, severe). Twenty-three patients (46%) had a satisfactory functional recovery, while twenty-seven (54%) had an unsatisfactory functional recovery rate. Conclusion. Surgical treatment of CSM is a very effective treating method and it resulted in a significant improvement in all outcome measures for a 1-year follow-up period. New studies could be recommended to evaluate the course of the disease, define the optimal surgical strategy, and better determine surgical outcome predictors.